Sociology And Society The Relevance Of Teaching Social Skills To Children For Communication - Ngozi Ugobueze, Ann (JURNAL ILMIAH MAHASISWA, 2024)
This study explores the relevance of teaching social skills to children as a means of enhancing communication and fostering positive social interactions within society. It emphasizes the importance of equipping children with essential social competencies such as active listening, cooperation, respect, and empathy from an early age. These skills are crucial for cognitive, emotional, and behavioral development, contributing to academic success and social cooperation. The study examines various strategies for teaching social skills in primary education, highlighting the role of teachers, caregivers, and the broader educational system in facilitating this process. It further discusses how social skills not only improve personal relationships but also address societal challenges by promoting social integration and cohesion. Additionally, the study identifies barriers such as socioeconomic and cultural factors that can hinder social skills acquisition and suggests practical approaches to overcoming these challenges. Ultimately, the research underscores the long-term benefits of social skills acquisition for children's future, including professional development, emotional intelligence, and overall well-being.